One Time Surgery in Contemporary Diseases of the Abdominal Wall and Pelvis in the Elderly - Giorgio Maria Paul Graziano; Carnazzo Santo; Samperisi Luigi; Antonino Graziano (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Introduction: The diseases most frequently found in the elderly are E.I. (inguinal hernia)* and BPH. (Prostatic hypertrophy non-neoplastic)*. The latter causes an effect on the abdominal wall to the increase in abdominal pressure from cervical-urethral obstruction, leading to the onset of the inguinal hernia pathology due to abdominal pressure which is higher, the greater as the residual bladder urine. The purpose of the study is to provide information on the surgical strategy and on timing in the presence of the simultaneous two diseases. Material and Method: Patients observed and joint treated were divided into two subgroups A (patients without) and B (patients with prosthetic implantation), with a mean age of 74 years. These patients accounted for 23% of the cases handled by hernioplasty and 49% of treated cases of BPH. The surgical treatment performed for joint pathologies in the two groups was that of a Pfannestiel single super-pubic incision extending on the projection of the inguinal ligament. In a first stage is performed a prostatic adeno-myomectomy sec Frayer, and subsequently an hernioplasty (prosthetic and do not). Results: The complications (seroma, hematoma) represented 10.6% of group A patients. In group B patients' complications attested to only 6% of cases, without a significant increase in complications or therapeutic failure, or a prolongation of hospital stay which was an average of 4 days and of 2 days in group A and B respectively. Early recurrent hernia, episodes that usually occur in the immediate postoperative period (prosthesis mobilization, throttling of the spermatic cord, etc.), we observe only 1% in group B, while present in 3% of patients in group A without affixing the prosthetic material. Finally the follow-up, implemented for a period of 24 -36 months to two groups, was sufficiently adequate for the purposes of a detection of possible late complications or relapses. Discussion: The affixing of the prosthesis thanks to the continuous evolution of materials and improved surgical technique favors the consolidation of early hernioplasty and the further reduction of the relapse rate. The simultaneous treatment of the two diseases in terms of satisfaction in patients treated has produced excellent results. Patients with only one operating session are not exposed to additional risks both anesthesia, and surgical, still burdened by complications Conclusions: The treatment of joint diseases EI ((inguinal hernia) and BPH (prostatic hypertrophy non-neoplastic) meets a great liking to the patient, for the adoption of a single analgesia to allow the implementation of both interventions in same day. Anatomical incision detects any non-clinically significant hernias, or unmask.